RANCANG BANGUN SISTEM PAKAR PEMBAGIAN WARIS BERBASIS WEB MENGGUNAKAN METODE FORWARD CHAINING - Naufal Ulumuddin, Muhammad; Heru Mujianto , Ahmad; Mashuri , Chamdan; Rusdyanto, Didiek (Inovate, 2025)
Inheritance law in Islam is commonly referred to as Faraidh. In the Islamic community, Faraidh is the science that deals with the distribution of inheritance. This subject is rarely studied, resulting in a lack of understanding among the public about Faraidh. This research aims to develop an expert system that can distribute inheritance according to those entitled to receive it. The expert system is web-based, using PHP programming language and MySQL database, and employs forward chaining reasoning and production rules (if-then rules) as the procedure for solving inheritance distribution. The methodology used is the waterfall methodology. The result of this research is an expert system that can distribute inheritance according to who is entitled to receive it, the amount of each share, the percentage of the total inheritance received from the net estate after deducting wills, funeral expenses, and debts. Keywords: inheritance, expert, Faraidh, forward chaining.